To assess the state of indicator species of small mammals in coastal habitats of rivers Zhetisu (Eurasian Journal of Ecology, 2016)
Averaged values of morphological and functional parameters show the similarity metric characteristics of rodents from survey locations with similar indicators of animals living in other regions of Kazakhstan. Level of functional load which are determinate by the indices of internal organs had similar values for populations. The more detailed study of this issue on a larger sample of wild animals is necessary. The results of studies the metric characteristics of rodents and hematological micronucleus test are close to the average statistical rate
Keywords: small mammals; morphological and functional parameters; hematology; micronucleus test.